PENGARUH VARIABEL RASIO KEUANGAN DAN MAKROEKONOMI TERHADAP PEMBERIAN KREDIT SEKTOR UMKM OLEH PERBANKAN DI INDONESIA - Raden Ai Lutfi Hidayat (Jurnal Manajemen dan Pemasaran Jasa, 2016)
The purpose of this study is to investigate the impact of financial ratios and macroeconomic variables toward SME’s credit on banking sector in Indonesia. In this research, financial ratio variables are the capital adequacy ratio, non performing loan, operating expenses per operating income, third party fund, return on assets, and business credit program. Macroeconomic variables is inflation, the gross domestic product, interest rate of working capital, and interest rate of investment. The research’s samples are banks in Indonesia that are divided based on their types in the period of 2004-2014. The method uses panel data multiple linear regression with random effect model. The results of this study are that CAR, NPL, and BOPO has a significantly negative effect on SME’s credit; DPK, ROA, KUR, inflation, and GDP have a significantly positive effect on SME’s credit. Interest rate of working capital has a significantly negative effect on SME’s credit and interest rate investments do not have a significantly effect on SME’s credit.